Postoperative Pain and Flare-Up Incidence Following Preparation with Rotary ProTaper and Single-File Reciprocating Systems: A Randomized Clinical Trial: Endodontic Postoperative Pain - Ashraf, Hengameh; Banazadeh, Yashar; Amiri, Maryam (Journal of Dental School, 2024)
Objectives Techniques used in root canal treatment (RCT) can cause postoperative pain. This clinical trial study aimed to compare the degree of postoperative pain following RCT using ProTaper Next rotary files and VDW reciprocating single-file systems. Methods Initially, a pilot study involving 10 patients in each group was performed to determine the final sample size. Sixty molars with irreversible pulpitis were randomly prepared using the Reciproc or ProTaper system. Postoperative pain severity was assessed using the Visual Analog Scale (VAS), categorizing pain level as no pain, mild, moderate, or severe before and immediately after treatment, as well as at 2, 6, 12, 24, and 48 hours postoperatively. Pain scores were analyzed using the Mann-Whitney U test to compare the two groups, and the impact of various factors on predicting postoperative pain incidence was assessed using PLUM ordinal regression (P < 0.05). The non-parametric Friedman test was used to evaluate differences in means before and after treatment. Results No significant differences were observed in pain score classifications between the Reciproc and ProTaper preparation systems before treatment, immediately after treatment, and at 2, 6, 12, 24, and 48 hours postoperatively. However, pain severity scores reported for the ProTaper system were slightly higher than those for Reciproc, with the difference becoming more noticeable 24 hours after treatment. None of the studied factors significantly predicted postoperative pain incidence. Conclusion Within the study's limitations and despite the absence of significant differences, using the single-file Reciproc system for tooth preparation appeared to yield slightly more favorable outcomes in alleviating postoperative pain of RCTs.